Analysis of the Influence of Knowledge and Work Environment on Patient Safety Culture With Attitude as a Mediating Variable in RSUD Serpong Utara - Mutiara Meilyn Pane; Anastina Tahjoo; Kemala Rita Wahidi (Lembaga Pengembangan Kinerja Dosen, 2026)
Patient safety culture is a critical component in healthcare organizations, reflecting the values, attitudes, competencies, and behavioral patterns that ensure safe patient care. This study aims to analyze the influence of knowledge and work environment on patient safety culture, with attitude serving as an intervening variable. A quantitative approach with an explanatory causal design was employed, involving 118 nurses as respondents selected through total population sampling. Data were collected using structured questionnaires and analyzed using Structural Equation Modeling with Partial Least Squares. The findings reveal that both knowledge and work environment have a significant direct effect on patient safety culture. Additionally, knowledge and work environment significantly influence attitudes, while attitudes themselves have a significant effect on patient safety culture. However, attitude does not mediate the relationship between knowledge and patient safety culture, but it does mediate the influence of the work environment on patient safety culture. These results indicate that improving nurses’ knowledge and creating a supportive work environment are essential strategies for strengthening patient safety culture. The study also highlights the importance of fostering positive attitudes through organizational support and conducive working conditions. The implications suggest that hospital management should focus on continuous training programs, enhancing workplace conditions, and developing systems that promote positive behavioral attitudes among healthcare workers to improve overall patient safety outcomes.